2021
DOI: 10.1002/rmb2.12365
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated cryopreservation and thawing using cryotip on the clinical outcomes of embryos

Abstract: Purpose To compare the clinical outcomes of embryo transfers that were cryopreserved and thawed two or three times with those cryopreserved and thawed once by CryoTip. Methods Data for 388 single cryopreserved‐thawed blastocyst transfer cycles, performed from April 2012 to March 2014, were assessed. The blastocysts were classified into three groups: blastocysts (A) cryopreserved once, (B) cryopreserved twice, and (C) cryopreserved three times. Results The pregnancy rate was 43.8% (134/306) in group A and 46.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…However, the developmental potential of embryos subjected to repeated freezing and thawing could be impaired despite the use of vitrification, a safe cryopreservation protocol. At present, most studies have observed that the pregnancy rate of twice-vitrified embryo transfer is comparable to the implantation and pregnancy rates of once-vitrified embryo transfer, which supports the safety and reliability of repeated vitrification [6][7][8][9][10]. In contrast, Aluko et al [11] have observed that in the PGT-A (preimplantation genetic testing for aneuploid cycle), biopsied blastocysts subjected to double vitrification had lower clinical pregnancy and live birth rates than once-vitrification blastocysts.…”
Section: Discussionmentioning
confidence: 86%
“…However, the developmental potential of embryos subjected to repeated freezing and thawing could be impaired despite the use of vitrification, a safe cryopreservation protocol. At present, most studies have observed that the pregnancy rate of twice-vitrified embryo transfer is comparable to the implantation and pregnancy rates of once-vitrified embryo transfer, which supports the safety and reliability of repeated vitrification [6][7][8][9][10]. In contrast, Aluko et al [11] have observed that in the PGT-A (preimplantation genetic testing for aneuploid cycle), biopsied blastocysts subjected to double vitrification had lower clinical pregnancy and live birth rates than once-vitrification blastocysts.…”
Section: Discussionmentioning
confidence: 86%
“…Our clinic has achieved favorable pregnancy rates with re‐cryopreserved and rethawed blastocyst transfer using CryoTip. 25 Therefore, in the re‐cryopreservation and rethawing of blastocysts, biopsy can be performed without any decrease in the quality of blastocysts. The second reason is the TE biopsy technique.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the establishment of cryopreservation and thawing techniques. Our clinic has achieved favorable pregnancy rates with re‐cryopreserved and rethawed blastocyst transfer using CryoTip 25 …”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that biopsies performed via the novel extrusion method did not affect the recovery of frozen–thawed blastocysts. Furthermore, a good pregnancy rate has been reported with refrozen–thawed embryos using a CryoTip, 11 suggesting the usefulness of performing biopsy using the n‐Ext method and freeze–thawing with a CryoTip.…”
Section: Discussionmentioning
confidence: 99%